EFFECT OF TANNERY SLUDGE IN MICRONUCLEUS FREQUENCY IN BIOINDICATOR Tradescantia pallida (Rose ) D.R. Hunt var. purpurea - GORNI, P.H.; GUANDALINI, C.R.; DA SILVEIRA, Z.V.; NAKAYAMA, F.T. (Revista Brasileira de Engenharia de Biossistemas, 2014)
The productive sector increasingly search the use of by-products and industrial waste as an economic and environmental alternative to productive sustainability. The tannery sludge is the main waste of leather industry is one of the most controversial waste used as fertilizer because it contains elements that can possibly come to contaminate soil and sub- soil. The objective of this study was to analyze the genotoxic potential of two types of tannery sludge ( liming and primary ETE ) in Tradescantia pallida microesporogenese of var. purpurea , considered indicator, using the micronucleus test ( TRAD - MCN ) . The micronuclei frequencies in control groups and between these and the group treated with liming sludge did not differ. Already the group treated with the primary sludge from WWTP significant difference in the frequency of micronuclei ( P < 0.001 ) compared to the other groups analyzed, suggesting genotoxic effects of chemicals to be detected after physical - chemical analysis of two types of sludge .